Wireless Mobility in Organizations Utilizing Social, Individual, and Organizational Intelligence - Clark, Stephen C. (Palgrave Studies in Democracy, Innovation, and Entrepreneurship for Growth,, 2018)
This book investigates the intuitive application of strategic knowledge arbitrage and serendipity (SKARSE) principles by CEOs in their use of mobile electronic devices. CEOs of small to mid-sized organizations are responsible for the income, expenses, and profitability of their respective division and rely heavily on mobile devices for learning, knowledge management, and communication. This book explores the effects of mobile devices on the individual CEO, their interpersonal relationships, and culture. It will benefit students, academics, and business professionals recognize events that can add to knowledge and enhance management skills. .